Recurrent pulmonary mucinous cystadenoma – case report - Kądziołka, Wojciech; Zamorski, Piotr; Kaznowska, Ewa; Kulig, Andrzej; Kądziołka, Joanna (Contemporary Oncology/Współczesna Onkologia, 2007)
Mucinous cystadenoma is a very rare lung tumour. Borderline malignancy, local recurrence and implantation in the place of the earlier resection are typical for mucinous cystadenoma. We report a case of a 60-year-old woman who had undergone colon resection because of adenocarcinoma of the rectum. After nine years there was found to be a tumour in the left lung lower lobe and lobectomy of that lobe was performed. The pathologist report confirmed mucinous cystadenoma. The next year after the previous pulmonary operation we recognized recurrence of the mucinous cystadenoma in the remaining ipsilateral lobe and removed it by wedge resection. Third left thoracotomy was performed two years after wedge resection on account of an upper mediastinal tumour which was excised and assessed by the pathologist as mucinous cystadenoma. The patient underwent a course of radiotherapy as a supplementary treatment.